Pengujian Black Box Menggunakan Teknik Equivalence Partitions Pada Aplikasi E-Learning Berbasis Web - Amalia, Amanda; Putri Hamidah, Salva Wanda; Kristanto, Titus (Forum Kerjasama Pendidikan Tinggi, 2021)
The quality of the software can be seen from the functionality of the application system whether it is in accordance with user needs or may be detrimental to system owners and users. For software testing, there are several methods used by testers to launch software, namely Black Box Testing and White Box Testing. In this study, the testing method used is Black Box Testing by applying Equivalence Partitioning to develop Web-Based E-learning applications at the Telkom Institute of Technology Surabaya because it is considered the most suitable for application testing by dividing the equivalence class into 2, namely valid and invalid classes. . The research stages are determining system functions, designing test cases, conducting tests, and drawing final conclusions. The results showed that this e-learning application screen was used as a distance or online learning medium at the Telkom Institute of Technology Surabaya.